From Space to Satisfaction: Investigating Architectural Interior Determinants of Quality Work Environments - Vesna Krizmanić; Aleksandra Milovanović (Buildings, 2025)
This study investigates the relationship between architectural attributes of workspaces and employee satisfaction, situating its inquiry within the broader context of post-pandemic hybrid work models and the evolving understanding of territoriality in organizational environments. Drawing on the social production of space and the multidimensional framework of Quality of Work Life (QWL), this research employs a quantitative, questionnaire-based methodology across three diverse corporate settings in Belgrade, Serbia. A total of 124 participants took part in the survey, representing the logistics (Fercam), IT (UBConnect), and healthcare (Medigroup) sectors. The survey integrates validated instruments—the Workspace Characteristics Scale (WCS) and the Workspace Satisfaction Scale (WSS)—to assess the impact of 12 variables and spatial features, reflecting functional, sensory, and sociological dimensions. Multiple regression analyses reveal that aesthetics, flexibility, and a sense of belonging consistently emerge as significant predictors of workspace satisfaction, with sector-specific variations observed across the cases. Notably, the findings underscore the importance of aligning spatial design with organizational values and user expectations while also highlighting the nuanced roles of sociological and psychological dimensions. The results offer practical relevance for architects and interior designers, providing insights into how design strategies tailored to user needs and sector-specific cultures can foster more effective workplace environments. This study concludes that evidence-based, multidimensional design strategies are essential for fostering well-being and productivity in contemporary work environments, demonstrating the value of aligning design with user expectations to enhance organizational outcomes. It recommends further research into the interplay between flexibility and belonging as determinants of workplace satisfaction.